Overview of Tuberculosis (TB) Cases in Banggai Regency, Central Sulawesi for the 2017-2019 Period - Sarni Tia; Wa Ode Monang (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Tuberculosis (TB) remains a major global health challenge, including in Indonesia, particularly in Central Sulawesi Province and Banggai Regency. This region continues to report a relatively high incidence of TB, influenced by multiple determinants such as environmental conditions and socio-economic disparities. Objective: This study aims to describe the trend of TB cases in Banggai Regency during 2017–2019 based on available secondary data. Methods: A descriptive quantitative approach was employed using secondary data from the Central Statistics Agency (BPS) of Central Sulawesi. Data on TB cases in Banggai Regency for the period 2017–2019 were analyzed descriptively and presented in tables and graphs. Patterns and trends were interpreted narratively to provide contextual understanding. Results: The analysis revealed an upward trend in TB incidence in Banggai Regency between 2017 and 2019. Contributing factors likely include environmental conditions, socio-economic constraints, and inadequate access to or quality of healthcare services. Conclusion: The rising trend of TB cases in Banggai Regency highlights the need for coordinated multisectoral interventions. Key factors such as limited healthcare access, poor socio-economic conditions, low treatment adherence, high population mobility, and improved reporting systems should be addressed. Further research and the implementation of effective, sustainable intervention strategies are urgently required. Keywords: incidence, global health, healthcare services, tuberculosis, Indonesia